Aesthetics and Rhetoric. - Gorbman, Claudia (American Music)
Focuses on the consideration of musical multimedia in terms of aesthetics and rhetoric. Aesthetic discourse in the examination of music for film especially in the art cinema; Scholarly paradigm of film studies; Rhetorical dimensions in the academic study of multimedia forms including television music and computer music.